Nitric Oxide Signaling in Plants - Hancock, John; Neill, Steven J. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue is a collection of research articles focused on the production and role of nitric oxide in plants. Nitric oxide is a crucial molecule used in the orchestration of cellular events in animals and plants. With a mixture of primary research papers and review articles written by some of the top researchers in the field, this work encompasses many aspects of this important and growing area of biochemistry.